2008
DOI: 10.1248/bpb.31.1032
|View full text |Cite
|
Sign up to set email alerts
|

Post-Transcriptional Regulation of Breast Cancer Resistance Protein after Intestinal Ischemia-Reperfusion

Abstract: Breast cancer resistance protein (BCRP), the product of the ABCG2 gene, is a recently identified ATP binding cassette half-transporter. BCRP is expressed in a variety of tumor cells and many normal human tissues. In the small intestine, BCRP can limit the influx and facilitate the efflux to prevent intracellular accumulation of BCRP substrates. Ischemia-reperfusion (I/R) induces the release of reactive oxygen species, and organs are severely damaged by I/R. It has been shown that the expression of transporters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A possible explanation for this discrepancy is that ABCG2 is post- transcriptionally and/or -translationally regulated in GBM cells such that RNA and protein levels do not correlate. Previous studies have reported that ABCG2 is post-transcriptionally regulated [26, 27]. In addition, others have reported that ABCG2 activity was predicted by its protein abundance and not by its mRNA expression [28].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this discrepancy is that ABCG2 is post- transcriptionally and/or -translationally regulated in GBM cells such that RNA and protein levels do not correlate. Previous studies have reported that ABCG2 is post-transcriptionally regulated [26, 27]. In addition, others have reported that ABCG2 activity was predicted by its protein abundance and not by its mRNA expression [28].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that Bcrp expression level in the apical membrane in the ileum after intestinal I/R was significantly decreased (25). These findings suggest that the decrease in BCRP expression at the apical membrane after intestinal I/R is caused by suppression of BCRP S-S bond formation.…”
Section: Discussionmentioning
confidence: 78%
“…In another study, the expression of Ab-cc2 in the liver was controlled by nuclear receptor activation, which is impaired during cholestasis (41). Abcg2 was found to play a role during oxidative stress, and its expression levels changed after IR injury in the kidney, liver, heart, cerebral vascular tissue, and intestines (42)(43)(44)(45)(46)(47). The levels of Abcc2 (Mrp2) expression in the rat liver decreased after IR injury, and endocytosis of Mrp2 developing in the canalicular membrane following IR caused impaired bile function (48).…”
Section: Discussionmentioning
confidence: 98%